Gut Microbial Metabolite Pravastatin Attenuates Intestinal Ischemia/Reperfusion Injury Through Promoting IL-13 Release From Type II Innate Lymphoid Cells via IL−33/ST2 Signaling - Deng, Fan; Hu, Jing-Juan; Yang, Xiao; Sun, Qi-Shun; Lin, Ze-Bin; Zhao, Bing-Cheng; Yao, Zhi-Wen; Luo, Si-Dan; Chen, Ze-Ling; Liu, Ying; Yan, Zheng-Zheng; Li, Cai; et al. (Frontiers in Immunology, 2021)
Intestinal ischemia/reperfusion (I/R) injury is a grave condition with high morbidity and mortality, we confirmed that intestinal I/R induces intestinal flora disorders and changes in metabolite, but the role of different metabolites in intestinal I/R injury is currently unclear. Based on targeted metabolic sequencing, pravastatin (PA) is a metabolite of the gut microbiota. Establishment of intestinal I/R model in mice through superior mesenteric artery obstruction. In addition, the co-culture model of small intestinal organoids and type II innate lymphoid cells (ILC2) were subjected to hypoxia/reoxygenation (H/R) to simulate an intestinal I/R model. The correlation analysis between the PA level in preoperative feces of patients undergoing cardiopulmonary bypass and the indices of postoperative intestinal I/R injury were carried out. IL-33-deficient mice, ILC2-deleted mice and Anti-IL-13 neutralizing antibodies were used to explore the potential mechanism of PA attenuating intestinal I/R injury. We demonstrated that PA, identified as a gut microbial metabolite, levels in preoperative stool of patients undergoing cardiopulmonary bypass negatively correlated with the indices of postoperative intestinal I/R injury. Furthermore, PA alleviates intestinal I/R injury and improves the survival of mice. We showed that PA promotes IL-13 release from ILC2 via activating IL-33/ST2 signaling to attenuate intestinal I/R injury. In addition, IL-13 promotes the self-renewal of intestinal stem cells by activating Notch1 and Wnt signals. Overall, we indicated that the gut microbial metabolite PA attenuated intestinal I/R injury through promoting the release of IL-13 from ILC2 via IL-33/ST2 signaling, revealing a novel mechanism and therapeutic strategy of intestinal I/R injury.